Designing cycling and running garments to increase conspicuity. Issue 3 (2nd September 2021) - Fylan, Fiona; Bentley, Laura A.; Brough, Dean; King, Mark; Black, Alex A.; King, Neil; Wood, Joanne M.
ABSTRACT: Poor conspicuity increases the risk of cyclists and pedestrians being involved in collisions with vehicles under low light conditions. Retroreflective strips in biomotion configuration significantly increases conspicuity. This study explored how to design biomotion garments that will appeal to cyclists and pedestrians. Nine focus groups involving 50 participants who ran/cycled under low light conditions. Participants discussed their experiences of choosing and wearing garments for cycling/running, and barriers to wearing biomotion garments. Using thematic analysis, we identified three themes. Design describes how biomotion garments should be attractive and practical. Function describes how they should be comfortable and convenient. Promotion describes participant's beliefs regarding cost and how to best explain the safety benefits of biomotion garments. Our user-centre research identified how to make biomotion garments appealing. Safety should not compromise design and function: users are unlikely to wear poorly designed and uncomfortable biomotion garments regardless of how much they increase conspicuity.